Population Development of the Invasive Species Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) on four Eucalyptus Species of the Subgenus Symphyomyrtus - Cuello, Eliana Marina (2018)
Thaumastocoris peregrinus Carpintero & Dellapé (Hemiptera: Thaumastocoridae) is a small sap-sucking insect that feeds on Eucalyptus L’Hér. leaves. Although it is native to Australia, it currently has a global distribution and it is considered as one of the big five pests of eucalypts around the world. We described the development of T. peregrinus population on four Eucalyptus species under the environmental conditions in Argentina. We also analyzed the use of yellow sticky traps as a monitoring method for this pest. The four Eucalyptus species were suitable for T. peregrinus. A cyclic pattern was observed in the development of the bronze bug population with an annual seasonal peak followed by a decrease in the abundance, reaching a minimum value during the unfavorable seasons. During the fall and winter seasons, epizootic events were registered in all the Eucalyptus species, caused by an entomopathogenic fungus. None of the meteorological variables had a clear influence neither on the bronze bug population nor with the occurrence of fungal infection. We found a significant relationship between the number of nymphs and adults of T. peregrinus in branches and the number of individuals caught in traps, suggesting that traps give actual information about the bronze bug abundance in the tree canopy.